2017
DOI: 10.1016/j.compfluid.2016.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Mixing in modulated turbulence. Analytical results

Abstract: Recent numerical results show that if a scalar is mixed by periodically forced turbulence, the average mixing rate is directly affected for forcing frequencies small compared to the integral turbulence frequency. We elucidate this by an analytical study using simple turbulence models for spectral transfer. Adding a large amplitude modulation to the forcing of the velocity field enhances the energy transfer and simultaneously diminishes the scalar transfer. Adding a modulation to a random stirring protocol will… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 23 publications
4
10
0
Order By: Relevance
“…In this manuscript, we have answered to the question whether a periodic modulation of a turbulent flow changes its mixing properties. It was clearly shown that for large modulation amplitudes, the modulation affects the energy transfer positively, whereas it diminishes the mixing rate, as was predicted in a recent analytical study (Bos and Rubinstein 2017). The average mixing rate was shown to decrease by approximately 20%, for two distinct Reynolds numbers, whereas the energy transfer rate increases by approximately 7%.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In this manuscript, we have answered to the question whether a periodic modulation of a turbulent flow changes its mixing properties. It was clearly shown that for large modulation amplitudes, the modulation affects the energy transfer positively, whereas it diminishes the mixing rate, as was predicted in a recent analytical study (Bos and Rubinstein 2017). The average mixing rate was shown to decrease by approximately 20%, for two distinct Reynolds numbers, whereas the energy transfer rate increases by approximately 7%.…”
Section: Discussionsupporting
confidence: 70%
“…In this summary we will only consider the case where the kinetic energy injection is modulated ¹ p 0, = q p 0, and where the modulation frequency is small. For the high frequency analytical results we refer to references (Bos et al 2007, Bos andRubinstein 2017).…”
Section: Summary Of Analytical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In periodically driven turbulence in shear flows, a meanfield theory has been used to analyze the resonance maxima of the Reynolds number [3,4]. Periodic forcing in other turbulent systems, for example, in the homogeneous isotropic turbulence [5][6][7][8], pipe flow [9][10][11][12], channel flow [13,14], Taylor-Couette flow [15,16], and Rayleigh-Bénard (RB) convection [17][18][19], is also shown to have highly nontrivial response properties.…”
mentioning
confidence: 99%